Regulation of Neutral Protease Productivity in Bacillus subtilis: Transformation of High Protease Productivity - Uehara, Hiroshi (1974)
A transformable strain of Bacillus subtilis 6160, a derivative of B. subtilis 168, produces three kinds of casein hydrolytic enzymes (alkaline protease, neutral protease, and esterase) in a culture medium. B. natto IAM 1212 produces 15 to 20 times as much total proteolytic activity as does B. subtilis. Extracellular proteases produced by the two strains were separated into each enzyme fraction by diethylaminoethyl-Sephadex A-50 column chromatography. The difference in the total protease activities of extracellular proteases between the two strains was due to the amount of neutral protease. The ratios of neutral protease activity to alkaline protease activity (N/A) were 1.1 in B. subtilis 6160 and 13.0 in B. natto IAM 1212. Enzymological and immunological properties of alkaline protease and neutral protease obtained from the two strains were quite similar or identical, respectively. Specific activities measured by an immunological analysis of the two neutral proteases against casein were also equal. A genetic character of high protease productivity in B. natto IAM 1212 was transferred to B. subtilis 6160 by the deoxyribonucleic acid-mediated transformation. Among 73 transformants that acquired high protease productivity, 69 produced a higher amount of neutral protease and the ratios of N/A were changed to 15 to 60. Three other strains were transformed in the productivity of neutral protease and α-amylase simultaneously, and one showed considerable change in the production of alkaline protease and neutral protease. The specific activities (casein hydrolytic activities/enzyme molecules) of neutral proteases from the representative four transformants were equal to those of the two parental strains. These results suggested the presence of a specific gene(s) that participated in the productivity of neutral protease in B. subtilis.